2017
DOI: 10.1090/proc/13692
|View full text |Cite
|
Sign up to set email alerts
|

A simplified Kronecker rule for one hook shape

Abstract: Abstract. Recently Blasiak gave a combinatorial rule for the Kronecker coefficient g λµν when µ is a hook shape by defining a set of colored Yamanouchi tableaux with cardinality g λµν in terms of a process called conversion. We give a characterization of colored Yamanouchi tableaux that does not rely on conversion, which leads to a simpler formulation and proof of the Kronecker rule for one hook shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…For partitions λ, µ, ν of nd let g(λ, µ, ν) ∈ N denote the Kronecker coefficient, i.e., the multiplicity of the irreducible S nd -representation [λ] in the tensor product [µ] ⊗ [ν], where [µ] ⊗ [ν] is interpreted as an S ndrepresentation via the diagonal embedding S nd ֒→ S nd × S nd , π → (π, π). A combinatorial interpretation of g(λ, µ, ν) is known only in special cases, see [Las80,Rem89,Rem92,RW94,Ros01,BO07,Bla12,Liu14,IMW15,Hay15], and finding a general combinatorial interpretation is problem 10 in Stanley's list of positivity problems and conjectures in algebraic combinatorics [Sta00]. In geometric complexity theory the main interest is focused on rectangular Kronecker coefficients, i.e., the coefficients g(λ, n × d, n × d).…”
Section: (A) Complexity Lower Bounds Via Representation Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…For partitions λ, µ, ν of nd let g(λ, µ, ν) ∈ N denote the Kronecker coefficient, i.e., the multiplicity of the irreducible S nd -representation [λ] in the tensor product [µ] ⊗ [ν], where [µ] ⊗ [ν] is interpreted as an S ndrepresentation via the diagonal embedding S nd ֒→ S nd × S nd , π → (π, π). A combinatorial interpretation of g(λ, µ, ν) is known only in special cases, see [Las80,Rem89,Rem92,RW94,Ros01,BO07,Bla12,Liu14,IMW15,Hay15], and finding a general combinatorial interpretation is problem 10 in Stanley's list of positivity problems and conjectures in algebraic combinatorics [Sta00]. In geometric complexity theory the main interest is focused on rectangular Kronecker coefficients, i.e., the coefficients g(λ, n × d, n × d).…”
Section: (A) Complexity Lower Bounds Via Representation Theorymentioning
confidence: 99%
“…In order to prove this theorem, we will derive a simple formula for these Kronecker coefficients, following the approaches set in [Bla12,Liu14,PP14b]. For brevity we set…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most remarkable of them is perhaps the family of Kronecker coefficients with a hook shape. Started in [46] and refined in [47], this program succeeds in giving g µνλ a combinatorial interpretation when one of the partitions, say µ, is a hook shape. In this section we will use their results to built a compact formula of Kronecker coefficients with a hook shape in terms of Littlewood-Richardson numbers.…”
Section: Tensor Partition Functionmentioning
confidence: 99%
“…In [47] it was shown that the Kronecker coefficients g µ(r)νλ can be expressed in terms of the standard inner products 1 of Schur and skew Schur functions as…”
Section: Tensor Partition Functionmentioning
confidence: 99%